Right Brain: Withholding treatment from a child with an epileptic encephalomyopathy. (1st May 2018) - Rothstein, Aaron; Lewis, Ariane
Abstract : The case of Charlie Gard, an infant who was hospitalized in England due to a mitochondrial DNA depletion syndrome that led to an epileptic encephalomyopathy, was highly publicized. Though Charlie's parents lobbied for him to receive experimental nucleoside replacement therapy as a desperate effort to save him, this request was denied, and after a lengthy legal battle, he died in late July 2017. We discuss the ethical considerations and consequences of this case.